Penerapan Strategi Tutor Teman Sebaya untuk Meningkatkan Hasil Belajar Pada Pembelajaran Pemesinan Bubut di SMKN 1 Kaligondang - Winarso, Didik; Santosa, Budi; Sahria, Yoga (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This research aims to improve the activity and learning outcomes of students in grade XI TP2 SMKN 1 Kaligondang through the Peer Teaching (Peer Tutor) learning method. The method used is Classroom Action Research (PTK) which is carried out in two cycles. Each cycle includes the stages of planning, implementation, observation, and reflection. The results of the study showed an increase in student learning activity from cycle I to cycle II with an average increase of 8.76%. In addition, student learning outcomes also increased with classical completeness reaching 88.88% in cycle II.